1995
DOI: 10.1159/000126885
|View full text |Cite
|
Sign up to set email alerts
|

Moderate Caloric Restriction Alters the Subcellular Distribution of Somatostatin mRNA and Increases Growth Hormone Pulse Amplitude in Aged Animals

Abstract: Although growth hormone secretion decreases with age in both animals and man, its potential role in the regulation of biological aging is unknown. In a series of experiments, age-related changes in growth hormone secretory dynamics were compared in ad libitum fed and moderately calorically restricted male Brown-Norway rats. These animals exhibit an increase in both mean and maximal lifespan in response to caloric restriction. In addition, the subcellular distribution of somatostatin mRNA was compared since pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
1

Year Published

1997
1997
2009
2009

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 7 publications
0
33
1
Order By: Relevance
“…IGF-I is also depressed (Underwood et al 1986, Vance et al 1992, Ohashi et al 1995 during fasting. It has been recently reported that impaired somatostatin distribution and release may also contribute to changes seen in the GH axis in nutritionally deprived animals (Aguila & McCann 1987, Sonntag et al 1995.…”
Section: Introductionmentioning
confidence: 99%
“…IGF-I is also depressed (Underwood et al 1986, Vance et al 1992, Ohashi et al 1995 during fasting. It has been recently reported that impaired somatostatin distribution and release may also contribute to changes seen in the GH axis in nutritionally deprived animals (Aguila & McCann 1987, Sonntag et al 1995.…”
Section: Introductionmentioning
confidence: 99%
“…One problem common to many studies on aging is that different animal strains are used and submitted to different nutritional conditions. It has been reported that moderate caloric restriction altered the subcellular distribution of SS mRNA and increased GH pulse amplitude in aged animals (53).…”
Section: Discussionmentioning
confidence: 95%
“…The synthesis and secretion of GHRH in the hypothalamus is thought to be reduced in aged rats fed ad libitum (23,24). There is no direct evidence that GHRH is secreted in aged DR animals in a fashion similar to that observed in young counterparts fed ad libitum However, a recent study reported that pulsatile secretion of GH similar to that in young AL rats is present in aged DR rats, but not in aged AL rats (25), suggesting that GHRH is secreted efficiently in DR rats in later life. Thus, preservation of the hypothalamic function may be attributed to maintaining the basal rate of somatotrope renewal in aging DR rats, leading to the protection of impaired pituitary response to GHRH during aging.…”
Section: Discussionmentioning
confidence: 99%